Formation of Ejecta and Dust Pond Deposits on Asteroid Vesta. Issue 11 (13th November 2021) - Parekh, R.; Otto, K. A.; Matz, K. D.; Jaumann, R.; Krohn, K.; Roatsch, T.; Kersten, E.; Elgner, S.; Russell, C. T.; Raymond, C. A.
Abstract: Dust and melt ponds have been studied on planetary bodies including Eros, Itokawa, and the Moon. However, depending on the nature of the regolith material properties and the location of the planetary body, the formation mechanism of the ponded features varies. On Eros and Itokawa, ponded features are formed from dry regolith materials whereas on the Moon similar features are thought to be produced by ejecta melt. On the surface of Vesta, we have identified type 1, ejecta ponds, and type 2, dust ponds. On Vesta type 1 pond are located in the vicinity of ejecta melt of large impact craters. The material is uniformly distributed across the crater floor producing smooth pond surfaces which have a constant slope and shallow depth. The hosting crater of melt‐like ponds has a low raised rim and is located on relatively low elevated regions. Whereas, the type 2 ponds on Vesta reveal an undulating surface that is frequently displaced from the crater center or extends toward the crater wall with an abruptly changing slope. We suggested that for the production of the type 2 ponds, localized seismic diffusion and volatile‐induced fluidization may be responsible for Vesta. Due to Vesta's large size (in comparison to Eros and Itokawa), the surface may have experienced local‐scale rare high‐amplitude seismic diffusion which was sufficient to drift fine material. Similarly, short‐lived volatile activities were capable to transfer dusty material on to the surface. Segregation and smoothing of transferred material lack further surface activities, hindering the formation of smooth morphology. Plain Language Summary: Ponded landforms are relatively smooth and featureless deposits and are commonly present on dry planetary bodies. The dry regolith of Eros, Itokawa, and the Moon provides ideal conditions for the formation of ponded deposits. They are produced either from the fine‐grained regolith substances or impact crater ejecta melt material. Typically, ponded deposits are distributed homogenously and produce a flat leveled deposit surface. However, due to lack of segregation mechanisms they do not always have an entirely flat topography. The production of ponded deposits relies on geological events that include regolith migration and various mechanisms have been proposed for their formation. In our study, we identify ponded deposits on the surface of Vesta and hypothesize that rare high‐amplitude seismic diffusivity and short‐lived volatile outgassing were responsible for the material migration and in turn for the production of ponded deposits. Key Points: We identified ejecta and dust pond crater candidates on Vesta within 0˚–30°N/S Ejecta ponds are smooth deposits and located within the ejecta melt of large craters Dust ponds are produced via local‐scale seismic shaking and/or volatile fluidization